THE QURANIC GUIDANCE FOR ADDRESSING THE FOOD CRISIS - Hadi Yasin; Abd Muid N (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
This research supports the theory of green economy. However, in the Quran, the concept of a green economy encompasses three important dimensions: Spiritual (Ruhiyah), Physical (Badaniyah), and Social (Ijtimaiyah). The Spiritual dimension includes values such as sincerity (Ikhlas), where every activity should be intended solely for Allah SWT, embodying the principles of Tawhid. Humans are merely custodians of the earth, not true owners. This dimension also includes the value of balance (Mizan), emphasizing the importance of balancing the relationship between humans and Allah (Hablun Minallah) and between humans and other beings (Hablun Minannas). This fosters sustainability, as illustrated in the story of Prophet Yusuf AS, promoting patience, steadfastness, and moderation in resource use to ensure the well-being of future generations. Leadership and trustworthiness (Amanah), described as khilafah in the Quran, also fall under this dimension, advocating for just, clean, and good governance. The Physical dimension includes the value of action (Harakiyah) for achieving blessings (Al-harakah-barakah) and the necessity to honor food as a provision from Allah, avoiding wastefulness (Israf), and promoting food saving practices. The Social dimension emphasizes equality and justice in addressing food crises, avoiding corruption, and preventing harm. The research aligns with opinions from figures and academics such as Antonio Guterres (FAO), Ahmad Mubariq (2010), Arief Anshory Yusuf (2018), Joel Makower (2008), Miguel Mendonca, David Jacobs, and Benjamin K. Sovacool (2009). It diverges from the views of anthropocentric scholars like Eugene Hargrove, Mark Sagoff, and Paul Burkett (2018, Red Economy theory). The study uses a qualitative method, gathering data from library research, and employs the thematic interpretation method (Tafsir Maudhû’i).